VERTICAL TEMPERATURE, THE FATE OF UP WELLING AND SPATIAL DISTRIBUTION OF FISH BIOMASS OF NORTH PAPUA WATERS - Agus Hartoko (JOURNAL OF COASTAL DEVELOPMENT, 2007)
The increasing need to introduce and highlight the analysis of deep water temperature (both horizontal and vertical) profile for up welling process and its relationship to fish biomass spatial distribution was inevitable. Especially to avoid the misleading interpretation of using only surface water temperature data for deep water fish biomass analysis.The paper analyze and revealed the fate / occurrence of up welling zone in adjacent of Halmahera islands through the analysis of both multi-layer horizontal and vertical temperature data. Further analysis on the temperature and fish biomass data revealed the close relationship of horizontal temperature pattern especially at depth of 80m with spatial distribution of total fish biomass (acoustic numeric data : in dB unit) and fish biomass (ton/mile square) with fish total-length above 30cm.